Pementasan Tari Jejumputan dalam Upacara Saba Nguja Benih - Widari, Tika; Sama, I Nyoman (Humanis; Vol 23 No 4 (2019), 2019)
Pedawa Village is one of Bali Aga Villages located in Banjar sub-district, Buleleng district which has a sacred ritual dance , name of this sacred dance is tari Jejumputan. This dance is usually performed once every five years when performing (sasih kaulu nemoning purnama) the ritual of Saba Nguja Benih . There are problems of study in this research, namely ( a ) How are the procredures of tari Jejumputan in the ritual of Saba Nguja Benih in Pedawa Village (b ) Function of the performance of tari jejumputan in the ritual of Saba Nguja Benih. This research is purposed to describe the performance of tari jejumputan in the event of the ritual of Saba Nguja Benih, and to unveil the function of the performance of tari Jejumputan in the ritual of Saba Nguja Benih in Pedawa Village. The theories used in this research are the theory of manifest and latent proposed by Robert K Merto n . Method used in this research is the qualitative research method. The techniques of collecting the data are observation, interview, and literature study. The technique of analysis used in this study is descriptive qualitative analysis. There are manifest and latent function in Jejumputan dance at Saba Nguja Benih ceremony. The manifest function contain important function namely to entertain Dewi Sri to get good seed, good harvest, deny the pest, and as a blessing for the bliss in agricultural sector. The latent function of Jejumputan dance is strength the solidarity among the society and as the identity of Pedawa Village.